Determining the cost-effectiveness of follitropin alfa biosimilar compared to follitropin alfa originator in women undergoing fertility treatment in France - Matthieu Lehmann; Elisangela Arbo; Jean-Luc Pouly; Paul Barrière; Lauren Amy Boland; Samuel George Bean; Julian Jenkins (Elsevier, 2024)
Objective: The study assessed cost-effectiveness of follitropin alfa biosimilar versus the originator in terms of cost per cumulative live-birth (CLB) for the French healthcare system based on real-world evidence. Follitropin alfa biosimilars have been shown to have comparable clinical outcomes to the originator, in both clinical studies and real-world settings, in terms of oocyte retrieval and cumulative live-birth rate (CLBR). Previous health economic studies comparing the cost-effectiveness of follitropin alfa biosimilars against the originator utilised clinical trial data, leaving ambiguity over cost-effectiveness in real-world settings. Additionally, previous cost-effectiveness analysis has been performed for live-births following only fresh embryo transfers, whereas, fresh and frozen transfers are common in clinical practice. This study investigates the cost per CLB, which more closely models clinical practice. Study design: A decision-tree cost-effectiveness model was developed based on the total costs and CLBR per ovarian stimulation (OS) for a follitropin alfa biosimilar (Bemfola®, Gedeon Richter Plc, Budapest, Hungary) and the originator (Gonal-f®, Merck KGaA, Darmstadt, Germany). A time horizon of one year from oocyte retrieval to embryo transfer was used but costs from resulting transfers were also included. Clinical inputs were taken from the REOLA real-world study or clinician insights, while acquisition costs were taken from French public databases. The output was cost per CLB following one OS. One-way sensitivity analysis was performed to determine the largest model drivers. Results: Cost per CLB was €18,147 with follitropin alfa biosimilar and €18,834 with the originator, saving €687 per CLB following OS with the biosimilar. When wastage estimates were considered the biosimilar cost saving is estimated to be between €796 and €1,155 per CLB further increasing cost savings. Irrespective of wastage, if used ubiquitously throughout France for ART, the biosimilar could save the French health system €13,994,190 or lead to 771 more births when compared to its higher-cost originator. Sensitivity analysis showed that the originator's relative CLBR had the greatest impact on the model. Conclusion: This analysis demonstrates that the follitropin alfa biosimilar, Bemfola®, is a more cost-effective option for OS compared with the originator from a French healthcare payer perspective, in terms of cost per CLB.